Selected Bibliographic Resources for the Promotion of Scientific Knowledge on the Websites of Libraries in Russia - A. V. Yuklyaevskaya (Библиосфера)
The purpose of the article is to show the results of a study of selected bibliographic resources in Russian libraries for the popularization of science, the promotion of scientific knowledge, the formation of a scientific worldview and the development of scientific literacy. Selected bibliographic resources on 87 library sites were considered. 750 selected bibliographic resources were identified, of which 280 (27 %) are aimed at disseminating modern scientific knowledge. Most of these are non-renewable resources. It has been established that in the process of promoting scientific knowledge, libraries most actively use reviews; electronic thematic collections, selections, exhibitions and selected lists; less often – selected bibliographic indexes, guidebooks, digests, card indexes and bibliographic reference books. Such traditional types of advisory aids as memos, bibliographic essays, popular bibliographic encyclopedias, booklets, and almanacs are almost never used. It is concluded that in the activities of libraries for the dissemination of scientific knowledge, selected bibliographic resources do not yet occupy a worthy place despite their decisive role in purposeful and systematically organized self-educational reading, which opens up wide opportunities for the formation of scientific worldview.